Understanding critical aspects of liposomal synthesis for designing the next generation targeted drug delivery vehicle - Moudgil, Aliesha; Chaudhari, Bhushan P. (Chemistryselect, 2023)
We identified process parameters of the thin film hydration technique and intrinsic factors to synthesize liposomes for drug delivery. The thin film formation step impacted the nature of the lipid layer, and we optimized 240 RPM rotation speed, 700 mm of Hg vacuum pressure, and 2 ml of chloroform as the organic solvent. The hydration step controlled the particle specifications, and we optimized 270 RPM rotation speed, PBS as the hydrating medium, and 1 h hydration time. We obtained a comparatively smaller liposomal population with a lower size distribution just after hydrating the lipid layer that required milder downsizing steps -10 extrusion passes through a single polycarbonate membrane. The intrinsic factors including the concentrations and molar ratio of lipids affected the synthesis steps and the particle specifications. Characterization of liposomes by analytical techniques confirmed the synthesis of a monodisperse population with hydrodynamic diameter<150 nm, moderate stability, spherical morphology, and high thermal and storage stability. This comprehensive study defines the role of every parameter, provides a mechanistic insight into synthesis that is supported by experimental data, and helps tune specific parameters to synthesize liposomes for drug delivery or any application with desired specifications.
Keywords: carrier system; designing and characterization; drug delivery; liposomes; targeting moiety